The Hyperbole in NCT Dream ISTJ Advertisement Video Using Dyadic Model - Hanifah Ardiani; Andang Saehu; Erlan Aditya Ardiansyah (Faculty of Humanities, Universitas Jenderal Soedirman, 2026)
This research analyzes the hyperbole meaning behind NCT Dream's